Answer:
A. -24
Step-by-step explanation:
we know that
A relationship between two variables, x, and y, represent a directly or proportional variation if it can be expressed in the form
or ![y=kx](https://tex.z-dn.net/?f=y%3Dkx)
In this problem we have
For x=-3, y=12
Find the value of the constant of proportionality k
![k=\frac{y}{x}](https://tex.z-dn.net/?f=k%3D%5Cfrac%7By%7D%7Bx%7D)
substitute the given values
![k=\frac{12}{-3}=-4](https://tex.z-dn.net/?f=k%3D%5Cfrac%7B12%7D%7B-3%7D%3D-4)
so
The linear equation is equal to
![y=-4x](https://tex.z-dn.net/?f=y%3D-4x)
what is the value of y when x=6?
substitute the value of x in the linear equation and solve for y
![y=-4(6)=-24](https://tex.z-dn.net/?f=y%3D-4%286%29%3D-24)
Answer:
the third one
Step-by-step explanation:
bc like there are 2 boxes of 1 and 5 boxes of 1/6 so thats already 2 and 5/6 which applies to all of them. then there is 1 box of 1 and 2 boxes of 1/3 so thats 1 and 1/3 which applies to all of them also but when you make them have the same denominator you get 2 and 5/6 + 1 and 4/6 which deletes the second one. When you add you should get the same denominator so that deletes the first one so then you simplify that and the fraction should still be equal to the unsimplified fraction so you should get 4 and 1/2 if that makes sense
Answer: Santa's speed in still air is 6 miles per minute
Speed of the wind is 1 mile per minute
Step-by-step explanation:
Let x represent the speed of Santa in still air. It is assumed that in still air. She is flying with the wind. If the speed of the wind is y, then him total speed is x + y
It takes Santa 5 minutes to fly 35 miles with the wind.
Speed = distance / time
It means that
x + y = 35/5 = 7
It takes him 7 minutes to fly 35 miles against the wind. This means that his total speed will be x - y
Speed = distance/time. Therefore,
x - y = 35 /5 = 5 - - - - - - 1
Substituting x = 7 - y into equation 1, it becomes
7 - y - y = 5
-2y = 5 - 7 = -2
y = -2/-2 = 1
x = 7 - y = 7 - 1
x = 6
Answer:
length : 15 ft
width : 3 ft
Step-by-step explanation:
perimeter = 2×l(ength) + 2×w(idth) = 36
l = 3w + 6
=> 2×(3w+6) + 2w = 36
6w + 12 + 2w = 36
8w = 24
w = 3
=> l = 3w + 6 = 3×3 + 6 = 9+6=15